Multi-parameter readout chip for interfacing with amperometric, potentiometric and impedometric sensors for wearable and point-of-care test applications. (June 2020) - Silverio, Angelito A.; Chung, Wen-Yaw; Tsai, Vincent F.S.; Cheng, Cheanyeh
Abstract: This work presents a multi-sensor readout system-on-chip (SoC) for interfacing with a multi-modal sensor array of amperometric, potentiometric and impedometric sensors. The individual readout circuits can be interfaced to external sensors such as screen printed electrodes (SPE), field effect transistor – based ion sensors such as the ion-sensitive FET (ISFET) and extended gate FET, and tetrapolar electrodes for electrical impedance spectroscopy (EIS). The chip features a method to avoid sensor cross-talk or interference between sensor modes despite a shared reference electrode and readout circuit. This is achieved through pass transistors as sensor selectors and as sub-circuit enables. The chip integrates high performance readout circuits with localized digital switches and a low dropout (LDO) regulator for high power supply rejection ratio (PSRR) bias. The chip has been fabricated using TSMC 0.18 ​μm 1P6M process and can serve as a mixed signal solution for interfacing with multiple sensor arrays for potential applications in point-of-care test and wearables.